(untitled) (Revista do Centro de Estudos Portugueses, 2006)
Em contraste com a poesia de Mario de Andrade e Carlos Drummond de Andrade, a experiência da vida urbana na obra de Mário Quintana é menos um motivo de euforia e desalento que de ambigüidade: neste artigo, relaciona-se essa ambigüidade com o caráter ambíguo da própria poesia de Quintana, entre o erudito e o popular, o moderno e o convencional, a prosa e o verso. The experience of urban life assumes, in Mário Quintana’ poetry, a different character in comparison to the works of other brazilian modernist poets, such as Mario de Andrade and Carlos Drummond de Andrade. Not an expression of enthusiasm or hindrance, Quintana’s verses reveal an ambiguity that can be related to the author’s own oscillation between prose and poetry, modernism and conventionalism, sophistication and directness.